The impact of filling procedure for labial augmentation (FPLA) therapy on the stability of lip print: A longitudinal study - Asmaa F. Sharif; Kawther AlShaikh; Nada AlQuraishi; Inas I. Abdelgawad (Forensic Science International: Reports)
Lip print identification is one of the forensic identification tools recognized a long time ago. Few studies investigated the stability of lip prints, particularly the changes attributed to time or aging. To our knowledge, no previous studies speculated the changes in lip print following lip augmentation therapy, which has increased over the last few years. Therefore, the current study aimed to investigate the effect of lip augmentation therapy on lip print stability. The current study was a prospective longitudinal study that enrolled female volunteers who underwent a filling procedure for labial augmentation. A total of 24 volunteers' prints were analyzed using Suzuki and Tsuchihashi classification. Participants showed a mean age of 27.5 ± 6.0 years. The current study showed that no two lips exhibited the same pattern. Moreover, although the filling procedure for labial augmentation (FPLA) therapy preserved the predominant groove pattern, it significantly influenced the frequency of lip patterns in all lip quadrants. A significant decline in the number of lip grooves, notably Types I and I' was noticed. However, the predominant groove pattern was preserved. Quadrants A and D were the least affected lip parts. Type I′ was the predominant lip pattern over the study population, representing 83.3 %, followed by Type I, representing 16.7 % before and 12.5 % after augmentation without a statistically significant difference (p = 0.317). On the other side, Type III was the least presented pattern. The upper lip score had decreased significantly after augmentation from 71.5 ± 10.8–65.8 ± 10.2, and the lower lip score had decreased significantly from 67.4 ± 13.7–64.9 ± 13.5. Consequently, the overall lips score had decreased significantly from 139.0 ± 22.9–130.7 ± 21.1 after augmentation (p < 0.001). So, we recommend adopting more than one criterion to report a reliable, repeatable lip print, including the frequency of lip lines besides the predominant pattern. However, we advise giving more attention to the distinguished lip patterns (Types II, III, IV, and V) and considering the FPLA as one of the lip print modifiers.